2017
DOI: 10.1039/c7ta02754k
|View full text |Cite
|
Sign up to set email alerts
|

A nanostructured nickel–cobalt alloy with an oxide layer for an efficient oxygen evolution reaction

Abstract: A nanostructured nickel–cobalt alloy with an oxide layer was fabricated with excellent oxygen evolution reaction activity and good stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 70 publications
2
45
0
Order By: Relevance
“…The benchmark catalysts for the OER are still noble metal catalysts, namely IrO 2 in acidic and RuO 2 in alkaline media. [18,19,24,27,[31][32][33][34][35][36][37][38] While the mechanisms of single metal catalysts are understood quiet well, the mechanism and the synergyo fb imetallic systems are less explored. Mn, [20][21][22][23][24] Fe, [24][25][26][27] Co, [6,24,[26][27][28] Ni, [24,26,27,29] and Cu [30] )a nd mixtures of such compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benchmark catalysts for the OER are still noble metal catalysts, namely IrO 2 in acidic and RuO 2 in alkaline media. [18,19,24,27,[31][32][33][34][35][36][37][38] While the mechanisms of single metal catalysts are understood quiet well, the mechanism and the synergyo fb imetallic systems are less explored. Mn, [20][21][22][23][24] Fe, [24][25][26][27] Co, [6,24,[26][27][28] Ni, [24,26,27,29] and Cu [30] )a nd mixtures of such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Mn, [20][21][22][23][24] Fe, [24][25][26][27] Co, [6,24,[26][27][28] Ni, [24,26,27,29] and Cu [30] )a nd mixtures of such compounds. [18,19,24,27,[31][32][33][34][35][36][37][38] While the mechanisms of single metal catalysts are understood quiet well, the mechanism and the synergyo fb imetallic systems are less explored. Rossmeisl et al showed that four consecutive energy steps are needed to create oxygen out of water.…”
Section: Introductionmentioning
confidence: 99%
“…C 1s peak at 284.8 eV was used as reference. [44][45][46][47][48][49] The corresponding satellite peaks are located at the higher binding energies . [44][45][46][47][48][49] The corresponding satellite peaks are located at the higher binding energies .…”
Section: Sem Xrd Xps and Tem Characterizationmentioning
confidence: 99%
“…In the high-resolution XPS (HRXPS) spectra of Ni 2p (Figure 2c), the binding energies at 852.8 � 0.1 eV and 856.2 � 0.1 eV are indexed to Ni 0 and Ni 3 + , respectively. [44][45][46][47][48][49] The corresponding satellite peaks are located at the higher binding energies . In the HRXPS spectra of Mo 3d (Figure 2d), the peaks at 228.2 � 0.2 eV, 229.2 � 0.2 eV, 230.3 � 0.2 eV, and 232.3 � 0.2 eV eV are indexed to Mo 0 , Mo + 4 , Mo + 5 , and Mo + 6 , respectively.…”
Section: Sem Xrd Xps and Tem Characterizationmentioning
confidence: 99%
“…9a-d. Various other alloys including NiCo, NiMo and Ni-B have also been explored as OER catalysts with promising results [112,115,116].…”
Section: Ni-based Alloysmentioning
confidence: 99%